2008
DOI: 10.1111/j.1365-2184.2008.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose tissue stromal vascular fraction cells differentiate depending on distinct types of media

Abstract: Here, we show that differentiation of SVF cells to endothelial cells or adipocyte-like cells depended on the medium used. Our work provides a clear model for analysing the differentiation capacity of SVF cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…These features permit a variety of stem cells and differentiated progeny, which respond to an assortment of signals that define the status of the skin and surrounding tissues. [22][23][24][25][26][27][28][29][30] Among these populations, mesenchymal stem cells have been shown to react to epithelial damage and assist in repair through a variety of mechanisms. The stromal vascular fraction, which harbors an assortment of mesenchymal stem cells/adipose-derived stem cells and progenitors, can be easily isolated, sustained in culture, and directed toward endothelial and angiogenic differentiation.…”
Section: Co-seeded Stromal Vascular Fraction To Lgr6 + Epithelial Stementioning
confidence: 99%
“…These features permit a variety of stem cells and differentiated progeny, which respond to an assortment of signals that define the status of the skin and surrounding tissues. [22][23][24][25][26][27][28][29][30] Among these populations, mesenchymal stem cells have been shown to react to epithelial damage and assist in repair through a variety of mechanisms. The stromal vascular fraction, which harbors an assortment of mesenchymal stem cells/adipose-derived stem cells and progenitors, can be easily isolated, sustained in culture, and directed toward endothelial and angiogenic differentiation.…”
Section: Co-seeded Stromal Vascular Fraction To Lgr6 + Epithelial Stementioning
confidence: 99%
“…New adipocytes develop from the recruitment and differentiation of preadipocytes into fully differentiated adipocytes. The preadipocytes are precursors of fat cells and reside in vascular stroma of adipose tissues [109].…”
Section: Role Of Il-18 In Hiv-associated Lipodystro-phic Syndrome (Hals)mentioning
confidence: 99%
“…16,17 The ASCs isolated from homogenized adipose tissue can proliferate, and differentiate into adipocytes. [15][16][17][31][32][33][34] Because the process converted aspirated fat that was relatively poor in ASCs into ASCs-rich fat, the transplanted fat had improved viability and maintained a consistent volume. Although Yoshimura et al demonstrated the potential clinical use of their method for soft tissue augmentation in breast augmentation and facial lipoatrophy, they did not report a laboratory method for verification the adipogenesis of SVF.…”
Section: Introductionmentioning
confidence: 97%